ASUHAN KEPERAWATAN MATERNITAS PADA NY. M DENGAN PEMBERIAN TERAPI JUS BUAH BIT UNTUK MENAIKAN KADAR HEMOGLOBIN DENGAN MASALAH RISIKO PERDARAHAN PADA IBU HAMIL DENGAN MASALAH ANEMIA DI RUMAH SAKIT HARAPAN BUNDA BATAM - Fadiya Wahyuni; Resi Novia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Anemia in pregnant women is a condition in which the mother has a hemoglobin (Hb) level in her blood of less than 11gr/dl as a result of the inability of the red blood cell-forming tissue to produce it to maintain the Hb concentration at a normal level. This scientific paper aims to provide Maternity Nursing Care to Mrs. M by Providing Beetroot Juice Therapy to Increase Hemoglobin Levels in Pregnant Women with Anemia Problems at Harapan Bunda Hospital, Batam in 2024. The method used in this scientific paper is a case study conducted based on the stages of nursing care including assessment, diagnosis, intervention,implementation, evaluation. The results of this scientific paper obtained the provision of beetroot juice for 5 days of giving the results of data analysis showed several diagnoses, namely the risk of bleeding related to pregnancy complications and fatigue related to anemia and the provision of beetroot juice therapy as one of the interventions that can be given to pregnant women who experience anemia to increase Hemoglobin levels in pregnant women Trimester III from Hb levels of 7.2 mg / dl to 11.9 with the criteria for the results of the patient does not feel a headache, does not feel weak in the body, the patient looks more relaxed and fresh.Therefore it can be concluded that intervention in beetroot juice can increase Hemoglobin in pregnant women who experience anemia. Suggestions for anemia sufferers in pregnant women to do non-pharmacological therapy of Beetroot juice in order to be able to increase Hb levels in pregnant women.Keywords: Anemia, Hemoglobin, Jus buah bit